Escherichia coli Mutants Tolerant to Beta-Lactam Antibiotics - Kitano, Kazuaki (1979)
Two types of Escherichia coli mutants tolerant to beta-lactam antibiotics were isolated. One is E. coli χ2452, which showed a tolerant response against beta-lactam antibiotics when grown at 42°C, and the others are the mutants C-80 and C-254, selected from mutagenized E. coli χ1776 by cycles of exposure to ampicillin, cephaloridine, and starvation of the nutritionally required diaminopimelic acid. Beta-lactam antibiotics caused rapid loss of viability and lysis in cultures of χ1776 or in χ2452 grown at 32°C. In contrast, the same antibiotics caused only a reversible inhibition of growth in mutants C-80 and C-254 or in cultures of χ2452 grown at 42°C. Beta-lactam antibiotics that show high affinity for penicillin-binding proteins 2 or 3 (mecillinam and cephalexin, respectively) induced similar morphological effects (ovoid cell formation and filament formation) in both parent and mutant strains. In contrast, beta-lactam antibiotics which have a high affinity for penicillin-binding protein 1 (e.g., cephaloridine or cefoxitin), which cause rapid lysis in the parental strains, caused cell elongation in the tolerant bacteria. In contrast to the parental cells, autolytic cell wall degradation was not triggered by beta-lactam treatment of χ2452 cells grown at 42°C or in mutants C-80 and C-254. The total autolytic activity of mutants C-80 and C-254 was less than 30% that of the parent strain. However, virtually identical autolytic activities were found in cells of χ2452 grown either at 42 or 32°C. Possible mechanisms for the penicillin tolerance of E. coli are considered on the basis of these findings.